2017
DOI: 10.1109/tnsre.2017.2707403
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Impedance Myography for Evaluating Paretic Muscle Changes After Stroke

Abstract: Electrical impedance myography (EIM) was used to assess the paretic muscle intrinsic electrical properties post stroke. Twenty-seven subjects with chronic hemiparesis participated in this study. Muscle impedance was measured by applying high-frequency, low-intensity alternating current to biceps brachii muscles. Major EIM parameters, resistance ( ), reactance ( ), phase angle ( ), and electrical anisotropy ratios (AR) of the three parameters, were examined at 50 kHz. Statistical analysis demonstrated significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 46 publications
(80 reference statements)
5
24
1
Order By: Relevance
“…Our measurements of |Z rest | ( Figure 14) converges with the ones from [25], where, after a set of exercises, the bioimpedance magnitude spectrum decreases for all frequencies. A drop in the bioimpedance real part when reaching fatigue was also reported in [22,24]. Albeit our project evaluated only one volunteer, the protocol ( Figure 2) was repeated 16 times, and the outcomes for all days were consistent.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Our measurements of |Z rest | ( Figure 14) converges with the ones from [25], where, after a set of exercises, the bioimpedance magnitude spectrum decreases for all frequencies. A drop in the bioimpedance real part when reaching fatigue was also reported in [22,24]. Albeit our project evaluated only one volunteer, the protocol ( Figure 2) was repeated 16 times, and the outcomes for all days were consistent.…”
Section: Discussionsupporting
confidence: 64%
“…Rutkove in 2002 made measurements to understand the mechanisms of impedance changes in neuromuscular diseases [21]. The resistance and reactance depend on the muscle length and cross-sectional area, so one can assume parameters such as muscle mass, shape and tissue quality defines the muscle impedance [22]. One of the major challenges of EBIM is to identify the contributions of each tissue (cutaneous, fat, muscle and bone) in the measurement [23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Applications of EIM to assess poststroke muscle conditions are relatively limited in the literature. In a previous study, we examined muscle impedance properties in the biceps brachii and found significant changes of muscle structural properties in the paretic side ( 24 ). Since proximal muscles demonstrate different extents of impairment from distal muscles ( 25 ), it remains unknown whether findings from biceps brachii are applicable to hand muscles.…”
Section: Introductionmentioning
confidence: 99%